Safety Maturity Level Assessment for Effective HSE Plan Development at Logistic Service Company in Ancol - Eka Cempaka Putri; Fierdania Yusvita; Decy Situngkir (The Indonesian Journal of Occupational Safety and Health)
Introduction: PT. XYZ is a logistics service company located at the Tanjung Priok port that carries out loading and unloading activities to support the operations of oil and gas companies. The achievement of leading indicators has been good. However, accidents still happen even though they are not as fatality accidents. This study aims to assess the maturity level of the Safety Culture at PT. XYZ and designing the right OHS program so that it is expected that the OSH program can reduce the number of lost time injuries in the company. Methods: This research is a qualitative descriptive study with a cross-sectional study design, and primary data was taken through interviews, field observations, and secondary data through company records. The author uses an interview guide from Industrial Safety Culture Evaluation Tools and Guidance for primary, key, and supporting informants. The main informants comprised five management representatives from supervisor to assistant manager level and five employee representatives. Results: PT. XYZ is a calculative level in safety culture, although the commitment dimension is in a proactive stage. However, information, awareness, and behavior are still at a calculative level. Conclusion: The company must improve communication methods, including effective communication, and provide consultation and training media for OHS issues.